The effect of gender, public accounting firm size, and company size on audit fee - Brian Fitra Herlano; Amelia Zulfani (Universitas Hayam Wuruk Perbanas, 2019)
An audit fee is the cost received by the auditor after completing his audit services. This fee is issued by a company who employ an auditor to increase management supervision, the quality of the company’s financial statements, and management independence. This study discusses several independent variables that have been used in previous studies, such as gender, the size of the Public Accounting Firm, and the size of the client’s company. This study aimed to determine the effect of gender, the size of the Public Accounting Firm, and the size of the client’s company on the audit fees in companies listed on the Stock Exchange in 2015-2016. This study uses a quantitative approach with a sample of 46 companies. The selection of samples in this study is conducted using a purposive sampling method. The data used are secondary data obtained from the Indonesia Stock Exchange (IDX). The analysis of the study is conducted using multiple linear regression analysis. The results of the study show that the size of the Public Accounting Firm and the size of the client’s company have an effect on the audit fee, while gender has no effect on the audit fees in companies listed on the Indonesia Stock Exchange ((IDX) in 2015-2016.